Standards for school principals in Mexico and Spain: A comparative study - Miguel Angel Díaz-Delgado; Inmaculada Garcia-Martinez (Arizona State University, 2019)
Both Spanish and Mexican education systems have been influenced by international standardized assessment programs, to the extent that both identify educational leadership as one of the main factors for school improvement; however, each national context has implemented dissimilar policies for developing standards for school principalship. Contrary to the global trend, in the Spanish context there is no homogeneous policy, each autonomous community determines the processes for access to and permanence in the school principals´ position. In contrast, the Mexican education system has developed robust standardization policies since the 2013 education reform. This study compares the standards for Principalship in the Spanish and Mexican public education systems, to consider (a) the processes for access to and permanence in the position (Gairín, 2010), (b) the institutional bureaucracy (Guiddens Sutton, 2014), and (c) the training for the principalship. This comparative analysis permits an exploration of the standards for school principalship in both education systems, recognizing the prior and current frames of reference in each context.